2011
DOI: 10.1021/ed101041n
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Implementation of a Problem-Based Learning Format in a Fourth-Year Undergraduate Synthetic Organic and Medicinal Chemistry Laboratory Course

Abstract: P roblem-based learning (PBL) is an educational approach that uses complex, real-world problems to motivate students to identify and research the concepts and principles that they need to know to devise a solution to the problem. 1 Students typically work in small groups, and while learning course content, other key abilities are developed including the ability to think critically; find, evaluate, and use appropriate learning resources; communicate effectively; and work independently of the instructor. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 13 publications
0
66
0
1
Order By: Relevance
“…PBL could effectively improve the motivation of students and ability to access and process information [18]. Research has suggested that the PBL experience for students might have a positive impact on academic achievement, conceptual development, and attitudes towards science courses [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…PBL could effectively improve the motivation of students and ability to access and process information [18]. Research has suggested that the PBL experience for students might have a positive impact on academic achievement, conceptual development, and attitudes towards science courses [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Students have little interesting in medicinal chemistry class. Certainly, the students learn medicinal chemistry not very well [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Advantages are that students feel more engaged, as projects are aligned to real-life problems, 4 and there is not necessarily a 'right' answer, as in real research. Indeed, it has been shown that the type of laboratory work affects views on the nature of scientific enquiry itself.…”
Section: Introductionmentioning
confidence: 99%